Intervenciones de enfermería en la prevención de la desnutrición crónica en menores de 5 años. - Cuno Pilco, Virginia Estefania (2024)
Chronic malnutrition in childhood represents a significant challenge for public health, affecting the growth and integral development of children. In this context, the role of nursing becomes essential, not only in the identification and monitoring of cases, but also in the practice of appropriate interventions. Therefore, the main objective of this research was to determine the nursing interventions to prevent chronic malnutrition in children under 5 years of age. To achieve this purpose, the following specific objectives were set: to identify the needs of these patients, as well as the main factors associated with this pathology and to design a nursing care plan based on the NANDA, NIC, NOC taxonomy. The methodology used is based on documentary, analytical and comparative research through the collection of information from different national and international databases. A sample consisting of 77 articles from 2019 to 2024 was used, selected intentionally and non-probabilistically, from which the necessary information was obtained to determine the nursing interventions required by these patients. Subsequently, a critical reading was carried out to synthesize the most relevant data and the information was analyzed by triangulating criteria to compare and contrast the ideas that address the problem of study from different points of view, obtaining as results that nursing interventions should focus mainly on adequate nutrition, maternal education, breastfeeding, psychosocial support, hygiene and monitoring of cases of malnutrition. Finally, the research concludes with the development of a care plan in a comprehensive and holistic manner, considering specific diagnoses and interventions in search of a better quality of life for children with chronic malnutrition.